Prognostic efficacy and prognostic factors of TACE plus TKI with ICIs for the treatment of unresectable hepatocellular carcinoma: A retrospective study - Han, Ziqiang; Yang, Faji; Zhang, Ye; Wang, Jianlu; Ni, Qingqiang; Zhu, Huaqiang; Zhou, Xu; Gao, Hengjun; Lu, Jun (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) remains a global challenge due to its high morbidity and mortality rates as well as poor response to treatment. Local combined systemic therapy is widely used in the treatment of unresectable hepatocellular cancer (uHCC). This retrospective study was to investigate the prognostic effect and prognostic factors of transcatheter arterial chemoembolization (TACE) plus tyrosine kinase inhibitors (TKI) with immune checkpoint inhibitors (ICIs) in the treatment of uHCC. A retrospective analysis of 171 patients with uHCC was performed in our hospital from April 27, 2015 to October 18, 2021. According to different treatment options, patients were divided into TACE group (n=45), TACE+TKI group (n=76) and TACE+TKI+ICIs group (n=50). In this study, we found that, the median overall survival (mOS) of TACE+TKI+ICIs group was significantly better than TACE+TKI group and TACE group [ 24.1 (95% CI 15.1-33.1) months vs 14.9 (95% CI 10.7-19.1) months vs 11.4 (95% CI 8.4-14.5) months, hazard ratio (HR) 0.62; 95% CI 0.47-0.81; P=0.002]. A visible difference in the median progression-free survival (mPFS) interval between the groups was discovered [10.6 (95% CI6.5-14.7) months in TACE+TKI+ICIs group vs. 6.7 (95% CI 5.5-7.9) months in the TACE+TKI group vs. 6 (95% CI 2.3-9.7) months in the TACE group (HR 0.66; 95% CI 0.53-0.83; P<0.001)]. The ORRs in the TACE group, TACE+TKI group, and TACE+TKI+ICIs group were 31.1%, 35.5%, and 42%, and the DCRs were 51.1%, 65.8%, and 80%. There were no AEs of arthralgia, diarrhea, rash, and pruritus in the TACE group. The incidence of grade 3 AEs (Hypertension) in the TACE+TKI+ICIs group was significantly higher than that in TACE+TKI and TACE groups (28% vs 17.1% vs 6.7%, P=0.024), and secondly, the morbidity of rash and pruritus in the TACE+TKI+ICIs group was apparently higher than that in the TACE+TKI group (P<0.05). Multivariate analysis showed that ECOG-PS 2 (HR=2.064, 95%CI 1.335-3.191, P=0.001), Hepatitis B virus (HR=2.539, 95%CI 1.291-4.993, P=0.007), AFP≥400 ng/ml (HR= 1.72, 95%CI 1.12-2.643, P=0.013), NLR≥2.195 (HR=1.669, 95%CI 1.073-2.597, P=0.023) were independent risk factors for OS in uHCC patients. So, TACE+TKI+ICIs therapy can prolong the OS and improve the prognosis of patients effectively, with a well-characterized safety profile.